KAJIAN PENGETAHUAN DAN PEMINAT BERMAIN MUSIK SASANDU DALAM KALANGAN MASYARAKAT KABUPATEN ROTE NDAO: KAJIAN PENGETAHUAN DAN PEMINAT BERMAIN MUSIK SASANDU DALAM KALANGAN MASYARAKAT KABUPATEN ROTE NDAO - Kataharina Kojaing; Stanislaus Sanga Tolan; Melkior Kian; Patricia Petrawati Saptono; Maria Marchindy Efliemsu; Petrus Nahak (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2024)
Sasandu is a traditional musical instrument typical of the people of Rote Ndao, NTT Province, and has become an icon of NTT province.   However, the activeness of the people of NTT, especially the people of Rote, in playing sasandu music seems to be lacking. It is very rare to find performances playing sasandu music. This research aims to determine knowledge and interest in playing sasandu music among the people of Rote Ndao district.  The research method was a survey and interviews with 440 respondents from four categories, namely: teenagers, parents, village government officials and arts activists, 110 people each. Respondents were found in 110 villages, in 11 sub-districts throughout Rote Ndao Regency, and in each sub-district at least 5 villages. Result of the research, data was obtained that all respondents knew about the sasandu musical instrument, had heard the sound of sasandu music, had watched people playing sasandu and knew that the sasandu musical instrument was an icon of the NTT province. All respondents also stated that they liked hearing the sound of sasandu music. In the aspect of those interested in playing sasandu music, data was obtained that among youth, parents, village officials and music activists, those who stated they wanted to play sasandu music were 43.63%, 16.35%, 25.45% and 83, respectively. 63%. Of this category of respondents, those who stated that they had tried to practice playing sasandu music were: 14.54%, 5.45%, 5.45% and 21.81%.